Belajar Dan Mengajar Dalam Perspektif Al-Quran - Nurry Marfu’ah; Alwizar (Jurnal Kajian Islam dan Sosial Keagamaan, 2024)
This article aims to find out more about the concept of teaching and learning and the principles contained therein based on the perspective of the Koran. Where the learning process will be easy and bring success if certain principles can be fulfilled. And the learning process can be in vain and fail if these principles are not met. This research uses a qualitative approach with a literature review type, with a focus on learning and teaching. The research results show that the essence of learning is the search and acquisition of knowledge, where it brings influence or change to students. Meanwhile, teaching can be interpreted as an activity or activities carried out by someone that can enable other people to know or master a certain knowledge.